Strategi Guru SD dalam Menghadapi Assesmen Kompetensi Minimum - Claraningtyas Silvia Damastuti; Aprilia Mia Rinjani; Margareta Vitaningksih (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2022)
Minimum Competency Assessment (AKM) is one part of the National Assessment (AN). The Minimum Competency Assessment focuses on two aspects of basic competence, namely reading literacy and numeracy literacy. Reading literacy does not only refer to students' reading ability, but also refers to students' reasoning power and critical thinking power. While numeracy literacy refers to the ability to think using concepts, procedures and facts to solve problems faced by student. One of the obstacles experienced in implementing this assessment program is the lack of readiness of elementary school teachers to face the Minimum Competency Assessment (AKM). Teachers need the right strategy to implement the Minimum Competency Assessment (AKM). Therefore, researchers conducted a study that aims to help teachers in overcoming these problems. This study aims to motivate elementary school teachers regarding the strategies used in dealing with the Minimum Competency Assessment (AKM).